A responsabilidade social como meio de legitimação em clubes brasileiros de futebol - Benin, Maicon Manoel (Universidade do Vale do Rio dos Sinos, 2025)
The sports sector, in general, and football, in particular, have been increasingly attracting attention, not only as a source of leisure but also as a business and vehicle for social transformation, raising the importance of topics such as Governance and Social Responsibility in these organizations. This research aims to determine how social responsibility practices, influenced by governance mechanisms, are used for legitimacy in football clubs. The analysis is based on the Legitimacy Theory, which considers that these organizations could use their social relevance and disseminate social responsibility practices as a means of legitimacy before the community where they operate, with this relationship moderated by the use of governance mechanisms. The research adopts a qualitative approach of an exploratory nature. The corpus of the research was composed of excerpts from interviews conducted with sports directors and executives and documents related to football clubs or associative sports organizations. The evidence was analyzed using the Discourse Analysis technique. The effects of the analyzed meanings allowed us to determine that social responsibility practices are used as components for the search for, maintenance of, or recovery of pragmatic legitimacy. This process makes these practices much more instrumental, as part of a system of exchanges between clubs and society than something institutionalized and a priority for these organizations. It was also identified that governance mechanisms intervene in this relationship, either by facilitating the instrumental use of social responsibility practices due to the lack of broad decision-making and supervision mechanisms or by encouraging the use of these practices as a genuine social commitment and good governance. Thus, this research contributes to understanding the role of governance and social responsibility in sports organizations, analyzing them together and exploring the nuances in the meanings that make up their complex motivations and relationships.
Keywords: Análise de discurso; Futebol; Governança; Responsabilidade social; Teoria da legitimidade; Discourse analysis; Football; Governance; Legitimacy theory; Social responsibility; ACCNPQ::Ciências Sociais Aplicadas::Administração